Income, employment, transfers, and household welfare dynamics before and during the conflict in Sudan - Ahmed, Mosab O. M.; Kirui, Oliver K.; Taffesse, Alemayehu Seyoum; Raouf, Mariam; Abushama, Hala; Siddig, Khalid (International Food Policy Research Institute, 2024)
This study examines the impact in Sudan of conflict on employment and incomes and the effect of remittances and assistance received by a household on its food insecurity and food consumption. The analyses use data from the 2022 Sudan Labor Market Panel Survey (SLMPS), the 2023 Sudan Rural Household Survey (SRHS), and the 2024 Sudan Urban Household Survey (SUHS). Conflict is found to significantly increase the likelihood of employment and income loss, particularly among female-headed and displaced households. Receipt of remittances does not have a significant effect on the food security or food consumption of a household. In contrast, whether a household receives assistance is associated with higher food insecurity and lower food consumption, likely reflecting the targeting of assistance programs toward vulnerable households. However, due to the cross sectional nature of the data, causal relationships cannot be established. The results highlight the need for targeted interventions to support the food security and welfare of households affected by the current conflict in Sudan, particularly through efforts to stabilize employment and incomes.